Bayesian neural networks - Bishop, Christopher (Journal of the Brazilian Computer Society, 1997)
Bayesian techniques have been developed over many years in a range of different fields, but have only recently been applied to the problem of learning in neural networks. As well as providing a consistent framework for statistical pattern recognition, the Bayesian approach offers a number of practical advantages including a solution to the problem of over-fitting. This article provides an introductory overview of the application of Bayesian methods to neural networks. It assumes the reader is familiar with standard feed-forward neural network models and how to train them using conventional techniques.
Special issue on neural networks